Research in the Social Scientific Study of Religion, Volume 16 - Piedmont, Ralph L. (Research in the Social Scientific Study of Religion, 2006)
Research in the Social Scientific Study of Religion (RSSSR) publishes reports of innovative studies that pertain empirically or theoretically to the scientific study of religion, including spirituality, regardless of their academic discipline or professional orientation. The articles included in this volume report studies on the role of religion and spirituality in relationship to many topics of current popular interest, among them well-being, self-esteem, emotional intelligence, substance abuse, social mobility, positive psychology, coping with medical decision making, and images of God.